Сто великих диктаторов - Мусский Игорь Анатольевич (100 великих, 2000)
Экземпляры: ФО-14 (201312) / Инвентарный номер: 48955 / Цена: 54.00 / Сис.шифр: 63.3(2)6-8 / Авт.знак: М 91 / ГРНТИ: 03 / ББК: 63.3(2)6-8